A Juridical Study On The Fulfillment Of Royalty Rights For Songwriters Or Music Composers Who Are Non-Members Of Collective Management Organizations Under The Applicable Laws And Regulations - Fhazar Arumba Ayodhya; Dwi Putra Jaya; Ferawati Royani (CV. Utami, 2026)
The fulfillment of royalty rights constitutes an integral part of the protection of the economic rights of songwriters and/or music composers as guaranteed under Law Number 28 of 2014 concerning Copyright. In practice, royalty management is conducted collectively through Collective Management Organizations (CMOs) and the National Collective Management Organization (LMKN) as regulated under Government Regulation Number 56 of 2021. However, the existence of songwriters or music composers who are not members of CMOs raises legal issues concerning legal certainty and the fulfillment of royalty rights arising from the commercial exploitation of their works. This research aims to analyze the legal regulation of royalty rights for non-member creators and to examine the authority of LMKN in collecting, administering, and managing the economic rights of such creators. This study employs normative legal research using statutory and conceptual approaches. Legal materials are analyzed qualitatively through systematic interpretation of relevant legislation. The findings indicate that royalty rights normatively arise automatically upon the creation of a work, without requiring membership in a CMO. Nevertheless, the distribution mechanism under Government Regulation Number 56 of 2021 does not explicitly guarantee the fulfillment of royalty rights for non-member creators, thereby creating potential legal uncertainty. Therefore, regulatory reinforcement is necessary to ensure fair, proportional, and non-discriminatory protection of economic rights.